How to Improve Students’ Science Learning Outcome? An Application of Problem-based Learning Worksheets - Erni, Erni; Yuberti, Yuberti (Indonesian Journal of Science and Mathematics Education, 2021)
The low of learning outcomes is a learning problem that is always encountered in various schools, including in SD (Primary School) Negeri 2 Campang Raya. The purpose of this study was to determine the differences and the effect of the use of problem-based learning worksheets on the learning outcomes of 4th-grade students at SD Negeri 2 Campang Raya. The research method used is quasi-experimental with a nonequivalent control group design. This study used non-probability sampling with 30 students in grade 4 at SD Negeri 2 Campang Raya as research subjects. Test and non-test instruments were used to collect research data and analyze data using t-test and simple linear regression. The results of the study indicate that there is an influence from the use of problem-based learning worksheets on the learning outcomes of 4th-grade students at SD Negeri 2 Campang Raya.